Painful Lesions in an HIV-1 Seropositive African Woman. - Stefano, Di Bella; Fabrizio, Taglietti; Nicola, Petrosillo (Journal of Clinical Research In HIV AIDS And Prevention, 2015)
A clinical case of painful mucocutaneous lesions in an HIV‑1 seropositive woman is presented. The report discusses differential diagnosis, diagnostic work‑up in resource‑limited settings, and targeted therapy considerations.